LEADERSHIP DEVELOPMENT EXPERIENCES OF DEPARTMENT CHAIRS AT A CANADIAN UNIVERSITY - Leda Stawnychko (Academic Chairpersons Conference Proceedings, 2020)
I will present the preliminary findings of a doctoral research study that explores the leadership development experiences of department chairs at a West Canadian university. The literature review, document analysis and themes emerging from semi-structured interviews with chairs of departments of diverse disciplines and sizes will also be explored.
Keywords: academic leadership; faculty development; chairpersons; department chairs; qualitative methods